ANALYSIS OF THE FUNCTION OF THE PROSPERITY'S COMMISSION IN SUPERVISING THE BEHAVIOR OF PROSPECTORS IN INDONESIA - Muhammad Fachrur Rozi (NOMOI Law Review, 2023)
With the power possessed by the Attorney General of the Republic of Indonesia, this institution has considerable powers in the field of prosecution and in administering state power. To minimize the occurrence of the Authority of State Power that exceeds the limit, usually, every State Institution must have limits through the Internal and External Oversight Board. It becomes a problem/issue when the external oversight agency, in this case, is the KKRI, where the results of the oversight carried out by the agency are in the form of recommendations, not followed up by the Attorney General or the President. The purpose of this study is to know the Authority of the Prosecutor's Commission and the legal consequences that arise in carrying out its duties and functions. The research method used is normative juridical. The results of this study are that the Prosecutor's Commission in Supervision has the authority to provide recommendations on alleged violations of ethics or the Prosecutor's behavior, but these recommendations do not have coercive power to be carried out like the form of supervision carried out by the Ombudsman which has juridical consequences if not implemented in the form of administrative to criminal sanctions, so it is necessary to strengthen normatively by providing legal consequences if the recommendation is not implemented by the Attorney General or the President.